Strategi Pengelolaan Usaha dan Harga Pokok Produksi untuk Memaksimalkan Laba - Sirewati, Sirewati; Nining, Nining; Solihah, Solihah (Journal of Community Development and Empowerment, 2025)
Efficient business management and accurate calculation of the cost of goods sold are crucial elements in maximizing company profits. This study aims to analyze effective business management strategies and approaches to determining the cost of goods sold as strategic steps to enhance profitability. The research method employed is a quantitative approach, involving the analysis of the company's financial data and interviews with business practitioners to identify factors affecting operational efficiency and the accuracy of production cost calculations. The study results indicate that resource management efficiency, production cost control, and the application of appropriate cost calculation methods, such as the full costing or activity-based costing methods, can significantly improve profit margins. Furthermore, the implementation of product diversification strategies and optimal supply chain management contributes to reducing operational costs and increasing market competitiveness. This study concludes that success in maximizing profits depends not only on sales volume but also on effective business management and accurate cost of goods sold calculations. Recommendations from this study include improving managerial competencies, developing supporting technologies for cost calculations, and periodically evaluating the company's operational performance.